Mechanical Contact Stress Analysis of Rollers at Various Hot Rolling Reductions Using Finite Element Approach - Hanafi, Agung Fauzi; Siregar, Ansor Salim; Wisnu Wardhaanaa, Prabuditya Bhisma; Mega Lazuardi Umar (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Hot rolling is a fundamental process in metal manufacturing; however, the operational integrity of the rollers is frequently threatened by excessive stress, which can lead to premature fatigue failure. This study aims to quantitatively analyze the effect of the cross-sectional reduction percentage on the distribution and magnitude of equivalent (von Mises) stress in hot rolling rollers. The Finite Element Analysis (FEA) method was employed to simulate the rolling process on rollers made of Ductile Cast Iron and a Structural Steel billet at a temperature of 800°C. Eleven simulation scenarios were executed by varying the reduction from 22% (industry standard) to 44%. The results indicate that the standard 22% reduction yields a very safe stress level (157.36 MPa), which is only 46.5% of the roller material's fatigue strength (338 MPa). It was found that roller stress increases non-linearly with increasing reduction, with a significant stress surge observed after a 41% reduction. The maximum safe operational limit was identified at a 43% reduction, which produced a stress of 275.43 MPa (81.5% of the fatigue limit). At a 44% reduction, the roller stress (369.37 MPa) exceeded the safe limit, indicating a high risk of component failure. This study provides a practical quantitative guide for the industry to optimize production throughput by establishing 43% as the maximum theoretical reduction limit.